Exploring the Perceptions and Practices of Ugandan Smes in Kabale Municipality Regarding Social Media for Brand Boosting - Sophan Niwamanya (Uganda Christian University, 2025)
The research is about exploring the perceptions and practices of Ugandan SMES in Kabale municipality regarding social media for brand boosting. The objectives of the study were identifying the social media platforms most commonly used by Ugandan SMEs for brand building, analyze the strategies and practices employed by Ugandan SMEs to enhance their brand image and engagement on social media, identify the main challenges faced by Ugandan SMEs in utilizing social media for brand boosting and understand how Ugandan SMEs measure the effectiveness of their social media efforts in terms of brand building. The research employed a descriptive case study approach to qualitatively investigate how chosen SMEs in Kabale Municipality utilize social media for brand enhancement, incorporating both primary and secondary information sources. The target population included SME owners, social media managers, and customers in Kabale Municipality. Purposeful sampling was applied to select 20 SMEs that actively participate in social media branding. Interview guides facilitated the collection of qualitative data from SME managers and marketers, while focus group discussions (FGDs) were held with SME staff and social media followers to gain insights into their shared perceptions and experiences concerning SME branding strategies on social media. During a focus group discussion with SME employees and social media followers in Kabale Municipality, they indicated that Facebook was the predominant platform for brand development.
Undergraduate Research